Microbiome changes through ontogeny of a tick pathogen vector. Issue 19 (18th September 2016) - Zolnik, Christine P.; Prill, Robert J.; Falco, Richard C.; Daniels, Thomas J.; Kolokotronis, Sergios‐Orestis
Abstract: Blacklegged ticks ( Ixodes scapularis ) are one of the most important pathogen vectors in the United States, responsible for transmitting Lyme disease and other tick‐borne diseases. The structure of a host's microbial community has the potential to affect the ecology and evolution of the host. We employed high‐throughput sequencing of the 16S rRNA gene V3‐V4 hypervariable regions in the first study to investigate the tick microbiome across all developmental stages (larvae, nymphs, adults). In addition to field‐collected life stages, newly hatched laboratory‐reared larvae were studied to determine the baseline microbial community structure and to assess transovarial transmission. We also targeted midguts and salivary glands due to their importance in pathogen maintenance and transmission. Over 100 000 sequences were produced per life stage replicate. Rickettsia was the most abundant bacterial genus across all sample types matching mostly the Ixodes rickettsial endosymbionts, and its proportion decreased as developmental stage progressed, with the exception of adult females that harboured a mean relative abundance of 97.9%. Laboratory‐reared larvae displayed the lowest bacterial diversity, containing almost exclusively Rickettsia . Many of the remaining bacteria included genera associated with soil, water and plants, suggesting environmental acquisition while off‐host. Female organs exhibited significantly different β‐diversity than the whole tick from which they were derived. Our results demonstrate clear differences in both α‐ and β‐diversity among tick developmental stages and between tick organs and the tick as a whole. Furthermore, field‐acquired bacteria appear to be very important to the overall internal bacterial community of this tick species, with influence from the host bloodmeal appearing limited.